Konsep Pembelajaran Ilmu Kaligrafi di Pondok Pesantren Modern - Fahrurrozi S; Yuyun Jelita Jabat; Sayed Muhammad Ichsan (Jurnal Sathar, 2024)
Calligraphy as a branch of art that has long roots, origins and history, besides having many kinds that show artistic peaks that attract attention because of their prowess, in Indonesia, calligraphy was present in line with the entry of Islam through trade routes in the 7th century M, then spread to remote parts of the archipelago around the 12th century AD. The method used is This research is included in qualitative research using a descriptive approach. Data sources are data from journals, library research methods with discussions about calligraphy (khat). Data collection techniques were carried out in three ways, namely: data collection, data reduction and drawing conclusions. The results of the study showed that Learning Calligraphy at Modern Islamic Boarding Schools uses many methods such as the lecture method, demonstration method, question and answer method, drill/assignment method, SAS method. , Field Trip Methods and Methods of Training and Practice.